PENGEMBANGAN LAMAN AUTOPROCTOR SEBAGAI DESKRIPSI TRUST SCORE DAN REAL SCORE PESERTA DIDIK PADA PEMBELAJARAN JARAK JAUH - Imron Maulana; Hindun Hindun (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2022)
The problem in this study is to determine the level of honesty and students' trust scores. This can be known by implementing the Autoproctor page. Of course, with interesting features on the page, be it the camera, audio, and tab switches, it will show concretely the extent to which the level of honesty and trust scores of students takes tests that have been designed by an educator beforehand. The research and development method for this page is a mix method, which emphasizes the integration of quantitative data with descriptions of each data presented. The results of the study show that the effectiveness of the Autoproctor page in representing the trust score and actual scores in the PJJ system is concretely credible and effective. This can be seen from each percentage of the trust score of students who commit acts of fraud. (3) the protection system from Autoproctor shows the score difference between the (temporary) exam result scores and the actual result scores (final grades). Therefore, the presence of the Autoproctor page through its various features, namely camera, audio, and tab switches, can provide answers to the concerns of educators and students, especially regarding the giving of